Design of Ditch Cleaning Machine - Chupak, Gerard; Azlan, Mohd Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The Design of Ditch Cleaning Machine project focuses on innovating a compact, efficient apparatus to maintain ditches crucial for managing water flow and preventing flooding. This initiative responds to the significant roles ditches play in safeguarding property, infrastructure, and agricultural productivity from waterlogging and disease spread. By following the structured George E. Dieter design process [1], including conceptual, embodiment, and detail design phases, the project aims to enhance existing technology for Malaysian conditions. Incorporating techniques like brainstorming and simulation, the project aims to optimize the machine's capability to clear aquatic vegetation and solid debris effectively. Simulation results demonstrate promising outcomes, with the machine weighing less than 80 kg and efficiently cleaning a 2000 m² area in just 2 hours. Ultimately, this effort seeks to advance environmental conservation and meet the diverse needs of ditch maintenance across Malaysia.